Hazardous Drug Contamination of Drug Preparation Devices and Staff: A Contamination Study Simulating the Use of Chemotherapy Drugs in a Clinical Setting. Issue 8 (September 2017) - Call, Evan; Bill, Brian; McLean, Chad; Call, Nathan; Bernkopf, Allyn; Oberg, Craig
Background: Hazardous drug contamination (HD) in healthcare environments continues, placing healthcare staff at risk of significantly chronic health problems, despite the use of personal protective equipment (PPE) and closed system transfer device systems (CSTDs).Objective: This study's aim was to determine how HD might spread through touch after handling contaminated vials in simulated pharmacy and nursing environments.Methods: UV fluorescent powder Glo Germ (Glo Germ Co., Moab, UT), composed of melamine resin, was used to simulate HD. Following manufacturer's exact usage specifications, five commercially available CSTDs were tested in the simulated pharmaceutical preparation environment under controlled conditions. UV fluorescence was used to detect the test medium powder that simulated HD following each trial. Photographs, using a Nikon D40X (10.2 mp) camera, were taken at selected stages of testing to document the presence of HD.Results: Transfer of the HD testing medium (Glo Germ) to IV sets, pharmacy PPE, and nursing PPE was observed in 4 of 5 CSTDs tested. The only CSTDs that showed no observable contamination was the Allison Medical Safety Enclosed Vial Adapter (SEVA) system (Littleton, CO).Conclusions: Results show residue from HD vials spread as vial was handled in a pharmacy environment in 4 of 5 CSTDs, contaminating pharmacy PPE, ancillary products, and nursing PPE. No HD residue was detected on PPE, ancillary products, or nursing PPE in the pharmacy after using the SEVA system, providing an effective means to contain HD for drug transfer from vial to delivery system.